Instalasi PLTS sebagai Sumber Energi Listrik untuk Usaha Peternakan Instalasi PLTS sebagai Sumber Energi Listrik untuk Usaha Peternakan Ayam Pedaging Masyarakat di Kecamatan Jakenan Kabupaten Pati Jawa Tengah - Trias Prima Satya; Imam Fahrurrozi; Galih Setyawan; Muhammad Rifqi Al Fauzan; Fitri Puspasari; Nur Rohman Rosyid; Prihadi Yogaswara; Alif Subardono; Sri Lestari; Estu Muhamad Dwi Admoko (Jurnal Pengabdian dan Pengembangan Masyarakat, 2019)
The community engagement programme of Solar Power Plant (PLTS) installation as an electrical energy source for broiler farming society business in Jakenan Subdistrict, Pati District, Central Java Province has been done. The aims of this programme helped the broiler farming society in that Subdistrict to increase their business production by utilizing the PLTS technology. The implementation of this community engangement was carried out by giving an example to install, maintain, utilize, and develop of PLTS system in one of the broiler cage. This programme was done from April 2018 until September 2018 continously. The result of this programme was installed the 3 x 100 wp PLTS system in one of the cage as an example. Furthermore, the broiler farming society in Jakenan Subdistrict, Pati District, Central Java Province were understood and abled to applicating the PLTS technology to increase their broiler business productivity.